Mitochondria in innate immunity signaling and its therapeutic implications in autoimmune diseases - Jiao, Yuhao; Yan, Zhiyu; Yang, Aiming (Frontiers in Immunology, 2023)
Autoimmune diseases (AIDs) are featured by their vast alterations in immune responses, however, the pathogenesis of which remains sophisticated and yet to be elucidated. Multiple mechanisms regulating cell differentiation, maturation and death can affect are found to be critical, among which mitochondria-related cellular organelle functions are recently gaining attention. Mitochondria as highly preserved organelle in eukaryotes, besides their function on chemical energy conversion, have crucial roles in the cellular response to stress, both exogenous and endogenous. In this review, we aim to summarize recent findings on the function of mitochondria in the innate immune response and its aberrancy in AIDs such as rheumatoid arthritis, systemic lupus erythematosus, etc., mainly focusing on its direct impact on cellular metabolism and its machinery on regulating immune response signaling pathways. More importantly, we summarize the status quo of potential therapeutic targets found in the mitochondrial regulation in the setting of AIDs and wish to shed light on future studies.